1994
DOI: 10.1159/000261996
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Uptake and Release Characteristics of Glass lonomer Cements

Abstract: The aims of this study were firstly to investigate the fluoride-releasing characteristics of five commercial glass ionomer materials: Ketac Fil, Chemfil Superior, Fuji II LC, Aquacem and Vitrebond. The second aim was to assess the fluoride uptake and subsequent release from the same range of materials. In both tests, ten discs, 6 mm in diameter with a thickness of 1.5 mm, were made for each material. The initial fluoride release was assessed over a 60-day period for all materials. Each disc was immersed in 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
1
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 9 publications
7
53
1
9
Order By: Relevance
“…They can adhere to enamel or metal substrates 16) , release and take up fluoride 17) , and inhibit microbial activity 18) . In the context of implant-supported restorations, cementretained restorations luted with provisional GICs have been used as a means of providing the patient with an esthetic prosthesis together with a suite of advantages such as appropriate retention, good antibacterial properties and biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…They can adhere to enamel or metal substrates 16) , release and take up fluoride 17) , and inhibit microbial activity 18) . In the context of implant-supported restorations, cementretained restorations luted with provisional GICs have been used as a means of providing the patient with an esthetic prosthesis together with a suite of advantages such as appropriate retention, good antibacterial properties and biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…23 To compare the present data with the results from other papers [24][25][26][27][28] involving a similar range of materials, the same unit (ppm) was chosen for comparison and discussion. The treatment of data by Rothwell et al 29 using mg/g for fluoride release versus the square root of time, assumes that fluoride release will be completely exhausted at infinity, and has gradually gained acceptance for recent publications of fluoride release.…”
Section: Researchmentioning
confidence: 98%
“…Geiger et al (1992) (Nicholson, 1998 It is well known that glass-ionomer cements release fluoride in vitro (Forsten, 1977). Creanor et al (1994) found that discs (6 mm in diameter and 1.5 mm thick) of Vitrebond (GIC) released a concentration of I55.2 ppm fluoride in 2 mL of deionized water at24…”
Section: 4 Null Ttrypothesismentioning
confidence: 99%